Construction of baculovirus transfer vectors for insect cell expression of human choline and ethanolamine kinase isoforms - Chang Chia, Than (Universiti Sains Malaysia, 2008)
Phosphatidylcholine and phosphatidylethanolamine are the most abundant phospholipid in eukaryotic cell membrane. Hwnan choline kinase and ethanolamine kinase play a very important role in the biosynthesis of phosphatidylcholine and phosphatidylethanolamine by catalyzing in the first phosphorylation step of the pathway. In this study, genes encoding hwnan choline kinase-P (hCK-P) and ethanolamine kinase-2P (hEK-2P) isoform gene fragments were inserted into newly constructed plasmid. The plasmid was constructed from commercially purchased transfer plasmid pBAC4x-1. Open reading frames (ORF) ofhCK-P and hEK-2P were introduced into the downstream of polyhedrin promoter for expression as histidine-tagged (his-tag) proteins. The constructs were ready for homologous recombination with Autographa californica Nuclear Polyhedrosis Virus (AcNPV) genome. Insect cells infected with the recombinant AcNPV were expected to overexpress the hCK-P and hEK-2P proteins.